Fiber Suspensions in Turbulent flow with Two-Point Correlation - Ahmed, SE; Sarker, MS Alam (Bangladesh Journal of Scientific and Industrial Research, 2011)
The equation of motion for turbulent flow of fiber suspensions has been derived in terms of correlation tensors of second order. Mathematical modeling of fiber suspensions in the turbulent flow is discussed including the correlation between the pressure fluctuations and velocity fluctuations at two points of the flow field, where the correlation tensors are the functions of space coordinates, distance between two points and the time. Keywords: Fiber suspension; Turbulent flow; Correlation. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8206 Bangladesh J. Sci. Ind. Res. 46(2), 265-270, 2011